(untitled) (Economics and region, 2024)
Local self-government in Ukraine is carried out on the principles of: democracy, legality, transparency, collegiality, combination of local and state interests, election, legal, organizational and material and financial independence within the limits of the powers defined by this and other laws, accountability and responsibility of their bodies and officials to territorial communities, state support and guarantees of local self-government, and judicial protection of the rights of local self-government. The article considers the issues of increasing citizens’ legal awareness and the development of democratic institutions in Ukraine, in particular in local councils. The author analyzes the state of national legislation, law enforcement and suggests specific measures to overcome problematic issues. A separate topic is the issue of usurpation of power as an illegal process that destroys the foundations of statehood. The concept of local government and its powers are defined. The mechanism of checks and balances of the local council is studied. The power of the city mayor is considered. The concept of "usurpation of power" is revealed. The authors offer effective mechanisms that help to understand the state of problems related to the concentration of power in communities at an everyday level. Democracy is a nationwide process that is in constant development. The effectiveness of democratic procedures at the local level (in territorial communities) is not a supplement to the generally accepted understanding of democracy as a way of organizing central government, but is an important component, an integral part of the state system. In developed democratic states, mechanisms of checks and balances in local councils are the basic (main) level of building state institutions. This is the foundation on which central government bodies are placed. Local democracy is a border bastion of ensuring human and citizen rights. The topic of the article is increasing the level of legal awareness of citizens at the local level, awareness of the essence, legal and political education of residents of specific territorial communities.